2012
DOI: 10.1007/s10904-012-9652-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Polyfunctional Cage Oligosilsesquioxanes and Cyclic Siloxanes by Thiol-ene Addition

Abstract: A novel octakis-2{ [3-(trimethoxysilyl)propyl] thio}ethyl-octasilsesqioxane (POSS-M24) was synthesized by radical thiol-ene addition of 3-mercaptopropyltrimethoxysilane, (MPTMS) to octavinyloctasilsesquioxane, (POSS-V8) in the presence of 2,2 0 azobisisobutyronitryl under mild conditions (60°C, toluene solution). Nano-building POSS units bearing both types of groups, 2-[3-(trimethoxysilyl)propylthio]-ethyl and vinyl, pendant to the POSS-cage were obtained by partial addition of MPTMS to the vinyl functions. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…The general features of the mechanism of this free radical process were described earlier [26,36,37,38,39]. In all cases studied the addition occurs with high yield and high selectivity according to the anti-Markovnikov rule.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations
“…The general features of the mechanism of this free radical process were described earlier [26,36,37,38,39]. In all cases studied the addition occurs with high yield and high selectivity according to the anti-Markovnikov rule.…”
Section: Resultsmentioning
confidence: 59%
“…We studied the thiol-ene addition of 6-mercapto-1-hexanol (MCH) to vinyl groups bound to silicon atoms of the silsesquioxane cage, initiated by 2,2′-azobisisobutyronitrile (AIBN). The general features of the mechanism of this free radical process were described earlier [ 26 , 36 , 37 , 38 , 39 ]. In all cases studied the addition occurs with high yield and high selectivity according to the anti-Markovnikov rule.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Multiple investigators have confirmed that the thiol‐ene reaction retains its “click” features in the presence of silicones; yet their work has generally been limited to the application of the thiol‐ene reaction rather than the characterization of its mechanism. Wijas and Chojnowski, for example, have verified that the thiol‐ene addition proceeds under mild conditions and reaches quantitative yields in the functionalization of silsesquioxanes 17. Moreover, Kim et al have documented rapid, homogenous network formation under ambient conditions without solvent or notable oxygen inhibition in the production of dielectric materials via photopolymerization of thiol‐ene functionalized oligosiloxanes 18.…”
Section: Introductionmentioning
confidence: 99%